2019
DOI: 10.1039/c9an00937j
|View full text |Cite
|
Sign up to set email alerts
|

Separation of isomeric glycans by ion mobility spectrometry – the impact of fluorescent labelling

Abstract: Bloodgroup oligosaccharides have been derivatized with labels common in HPLC and evaluated regarding their ion mobility behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…To create the dextran calibration ladder, a 1:1 mix of dextran 5000 and dextran 1000 was dissolved in 20 μL water. Afterwards, both the released glycans and the dextran mix were labeled with procainamide according to established protocols [ 7 , 14 ]. The labeled glycans were purified with the Discovery Glycan SPE tubes according to vendor’s instruction, dried via SpeedVac (Thermo Fisher Scientific, Waltham, USA) and further suspended in 50 μL water before storing them in the HPLC autosampler at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To create the dextran calibration ladder, a 1:1 mix of dextran 5000 and dextran 1000 was dissolved in 20 μL water. Afterwards, both the released glycans and the dextran mix were labeled with procainamide according to established protocols [ 7 , 14 ]. The labeled glycans were purified with the Discovery Glycan SPE tubes according to vendor’s instruction, dried via SpeedVac (Thermo Fisher Scientific, Waltham, USA) and further suspended in 50 μL water before storing them in the HPLC autosampler at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Due to its importance, monitoring of N -glycosylation is a crucial requirement in the characterization of therapeutic antibodies [ 2 ] and also gained increased attention to identify potential biomarkers for cancer and other diseases [ 3 5 ]. The characterization of N -glycans usually requires the cleavage of the glycans from the protein and a subsequent reducing end modification with a fluorescent label [ 6 , 7 ]. The following analysis is often based on liquid chromatography (LC) in combination with fluorescence (FLD) or mass spectrometry (MS) detection [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…IMS, often hyphenated with front-end analytical techniques of chromatography and coupled with MS, has been widely known for its application on isomers/isobars separation. In cases of isomeric compounds that are not separated in the chromatographic dimension and not distinguished by MS, ion mobility offers an additional dimension of separation while amplifying peak capacity . IMS-based methodologies in the field of food authenticity are still unexploited, with a limited number of studies being reported so far. These studies are mainly focused on targeted or semitargeted approaches, with untargeted implementation being hampered by the lack of integrated workflows to deal with such complex and large data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the molecular features of polysaccharide digests sometimes are not obviously different for the recognition and differentiation of polysaccharide species. 16,17 Therefore, a simple, effective, and efficient analytical method that can produce fingerprint spectra with characteristic signals is needed for polysaccharides' quality control and product evaluation. Direct analysis of intact polysaccharide using MS is difficult because there are no suitable ionization methods.…”
Section: Introductionmentioning
confidence: 99%